PKM WORKSHOP MEMBANGUN USAHA RINTISAN BERBASIS TEKNOLOGI DI SMK NEGERI 3 NEGARA - Ida Bagus Kade Dwi Suta Negara; Ida Ketut Kusumawijaya; Ketut Yudana Adi; Putu Kusuma Negara (Universitas Triatma Mulya, 2023)
In the era of globalization and rapid technological developments, it is important for SMK (Vocational High School) students to have skills and knowledge relevant to the industrial world. One way to prepare SMK students to face this challenge is through community service activities. The Workshop on Building a Technology- Based Startup at SMK Negeri 3 Negara was initiated as a community service activity (PkM) to overcome these obstacles. The implementation of the PkM workshop on Building a Technology-Based Startup for Students of SMK Negeri 3 Negara is divided into several stages including: problem identification, activity implementation, and evaluation stage. In general, the implementation of this activity went according to plan, this was evidenced by the results of the questionnaire, the program partners answered that they were satisfied with the implementation of this program.